God dwells with His people a study of Israel's ancient tabernacle - Zehr, Paul M. 1936- (Scottdale, PA Herald, 1981)
Includes bibliographical references and indexes.
Keywords: Tabernacle -- study and teaching; Bible. O.T. Exodus -- criticism, interpretation, etc; Bible. O.T. Exodus -- typology